On-chip photodynamic therapy – monitoring cell metabolism using electrochemical microsensors. Issue 22 (12th October 2018) - Marzioch, Julia; Kieninger, Jochen; Weltin, Andreas; Flamm, Hubert; Aravindalochanan, Kuppusamy; Sandvik, Joe A.; Pettersen, Erik O.; Peng, Qian; Urban, Gerald A.
Abstract : Metabolic monitoring of T-47D breast cancer cells using electrochemical microsensors combined with photodynamic therapy on-chip. Abstract : We introduce a new system which combines metabolic monitoring using electrochemical microsensors with photodynamic therapy on-chip for the first time. Oxygen consumption of T-47D breast cancer cells was measured during therapy with protoporphyrin IX. We determined the efficacy of the therapy and revealed its recovery effects, which underlines the high relevance of continuous monitoring.